Determinants of Accounting Information System in pt. Indomarco Adi Prima, Jember Branch - Rina Dian AGUSTIN; Muhammad FIRDAUS; Nanda WIDANINGGAR (Indonesia Strategic Sustainability, 2020)
The fundamental role of Accounting Information Systems (AIS) in organizations was a processor of accounting data to produce quality accounting information to support the company's internal activities, which had a significant correlation with the external. By the purposive sampling method, this study aims to analyze the impact of Education and Training Programs, Involvement of System Users, and Human Resources (HR) Competence on the Quality of Accounting Information Systems at PT. Indomarco Adi Prima Jember Branch, since there were ineffective process in selling application, by the late of manager approval and the network problem. The population in this study were all of employees who use Information Systems at PT. Indomarco Adi Prima Jember Branch. The method used was multiple regression, the data collection technique was questionnaire, and the result showed that the variable Education and Training Program significantly influences the quality of the AIS, System User Involvement variable significantly influences the quality of SIA, and HR competency variable significantly influences the quality of SIA and the coefficient of determination (R2) of all independent variables strongly explained the dependent variable.